The Development of Learning Activities to Promote Critical Thinking Skills using Marzano's Learning Management Technique for Six Grade Students - Phimphisan, Piyaphon; Chanthachum, Natthachai; Chanprathuk, Anusorn (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2020)
The objectives of the research article were to 1) analyze, synthesize the guidelines for the development of learning activities. for six Grade Students. 2) Develop learning activities, enhance critical thinking skills for six Grade students. 3) For experimenting and evaluating critical thinking skills Of students after school by using learning activities to promote critical thinking skills for six Grade Students and 4) students in order to assess the students' satisfaction in organizing learning activities, promoting analytical thinking skills for six Grade Students, the target group used in the experiment is for six Grade Students in the 2nd semester of the academic year 2017 at Ban Nong Bua Noi School, 31 people, selected by specific selection the instrument used in the research was an interview form about the guidelines for learning activities. Learning management plans to promote analytical thinking skills of prathomsuksa six students, analytical thinking skills test Satisfaction questionnaire Data analysis using percentage, mean, standard deviation. And use the Wilcoxon Signed Rank Test. The research found that : 1) Guidelines for the development of learning activities to enhance analytical thinking skills are to organize learning activities to promote analytical thinking skills with techniques, methods, or teaching styles that enable students to have knowledge and ability in Study better There should be a teaching process with various learning activities to train students to improve their critical thinking. The researcher used Marzano's concepts in designing learning activities. Which is an appropriate method and also a teaching method that uses knowledge and ability to develop critical thinking skills. 2) The results of the development of teaching and learning activities to promote critical thinking skills for six Grade Students that were created, divide the content into 5 learning management plans for 25 hours. Each plan consists of Learning standard/key indicators, learning objectives Learning activities learning Media Measurement and evaluation and each plan has work sheets and post-test The evaluation result of the appropriateness of the learning activity plan was at a high level. The effectiveness of the learning management plan to promote analytical thinking skills for PrathomSuksa six Grade Students it is equal to 81.19 / 83.39 which is higher than the specified criteria. 3) The results of the trial and evaluation of learning activities to promote analytical thinking skills for six Grade Students with pre-school scores with an average score of 16.12 and an after-school average score of 25.12 and when comparing between scores Before school and after school It was found that the test scores after learning activities were significantly higher than before learning activities at the .01 level, and 4) satisfaction with organizing learning activities, promoting analytical thinking skills for six Grade Students in the highest level.